New species of dung beetles (Coleoptera: Scarabaeidae: Scarabaeinae) from Mexico and Costa Rica - Kohlmann, Bert; Solís, Ángel (Zootaxa, 2006)
The following new species of dung beetles (Coleoptera: Scarabaeidae) are described: Canthidium margaritae sp. nov. from Mexico and Canthon inusitatus sp. nov. from Costa Rica. Illustrations of the dorsal habitus and distribution maps are provided for both species.